Experiences and lessons learned for programme improvement of micronutrient powders interventions. (29th September 2017) - Vossenaar, Marieke; Tumilowicz, Alison; D'Agostino, Alexis; Bonvecchio, Anabelle; Grajeda, Ruben; Imanalieva, Cholpon; Irizarry, Laura; Mulokozi, Generose; Sudardjo, Minarto Noto; Tsevegsuren, Narantsetseg; Neufeld, Lynnette M
Abstract: Continual course correction during implementation of nutrition programmes is critical to address factors that might limit coverage and potential for impact. Programme improvement requires rigorous scientific inquiry to identify and address implementation pathways and the factors that affect them. Under the auspices of "The Micronutrient Powders Consultation: Lessons Learned for Operational Guidance, " 3 working groups were formed to summarize experiences and lessons across countries regarding micronutrient powder (MNP) interventions for young children. This paper focuses on how MNP interventions undertook key elements of programme improvement, specifically, the use of programme theory, monitoring, process evaluation, and supportive supervision. Methods included a review of published and grey literature, interviews with key informants, and deliberations throughout the consultation process. We found that although much has been written and published about the use of monitoring and process evaluation to inform MNP interventions at small scale, there has been little formal documentation of lessons for the transition from pilot to scaled implementation. Supervision processes and experiences are not documented, and to our knowledge, there is no evidence of whether they have been effective to improve implementation. Improving the efficiency and effectiveness of interventions requires identification of critical indicators for detecting implementation challenges and drivers of impact, integration with existing programmes and systems, strengthened technical capacity, and financing for implementation of effective monitoring systems. Our understanding of programme improvement for MNP interventions is still incomplete, especially outside of the pilot stage, and we propose a set of implementation research questions that require further investigation.